2002
DOI: 10.1590/s0036-46652002000600004
|View full text |Cite
|
Sign up to set email alerts
|

Conventional and molecular typing of Salmonella typhi strains from Brazil

Abstract: Phenotypic and genotypic characteristics of Salmonella Typhi were studied in 30 strains, isolated in different years, from some areas in Brazil. Conventional typing methods were performed by biochemical tests, Vi phage-typing scheme, and antimicrobial susceptibility test. Molecular typing methods were performed by analysis of plasmid DNA and by random amplified polymorphic DNA (RAPD-PCR). For the latter, an optimization step was performed to ensure the reproducibility of the process in genetic characterization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 25 publications
3
11
0
5
Order By: Relevance
“…Thus, the use of random amplification of polymorphic DNA fingerprinting technique (RAPD), a modification of the polymerase chain The number and the intensity of fragments produced varied in function of the thermal cycling profile, the MgCl 2 , DNA template, primer and Taq DNA polymerase enzyme concentrations. Maintaining the DNA and primer 784 concentrations at 20ng/µl and 20pM/µl, respectively, and varying the MgCl 2 concentration, we observed that the best fingerprinting pattern was obtained using 2.0mM MgCl 2 at reaction (PCR) in which arbitrary oligonucleotides primers are used to promote DNA synthesis at low stringency conditions in order to determine genomic diversity, may be considered a promising alternative typing method capable of discriminating between S. enterica serovar Typhi strains of the same phage type 14 . Besides differentiating isolates of serovar Typhi and other Salmonella isolates, RAPD-PCR proved capable of discriminating between S. enterica serovar Typhi strains 16 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the use of random amplification of polymorphic DNA fingerprinting technique (RAPD), a modification of the polymerase chain The number and the intensity of fragments produced varied in function of the thermal cycling profile, the MgCl 2 , DNA template, primer and Taq DNA polymerase enzyme concentrations. Maintaining the DNA and primer 784 concentrations at 20ng/µl and 20pM/µl, respectively, and varying the MgCl 2 concentration, we observed that the best fingerprinting pattern was obtained using 2.0mM MgCl 2 at reaction (PCR) in which arbitrary oligonucleotides primers are used to promote DNA synthesis at low stringency conditions in order to determine genomic diversity, may be considered a promising alternative typing method capable of discriminating between S. enterica serovar Typhi strains of the same phage type 14 . Besides differentiating isolates of serovar Typhi and other Salmonella isolates, RAPD-PCR proved capable of discriminating between S. enterica serovar Typhi strains 16 .…”
Section: Discussionmentioning
confidence: 97%
“…As described previously 14 . It has been demonstrated that RAPD-PCR reaction has the potential to provide a discriminatory, reproducible and easy to interpret method to type S. enterica serovar Typhi strains.…”
mentioning
confidence: 99%
“…PCR-based fingerprinting using RAPD has been used widely for genome identification, and the RAPD technique using up to six primers has been reported to be a good tool for molecular typing, permitting the execution of public health measures necessary to control infection (Chansiripornchai et al, 2000;De Cesare et al, 2001;Khoodoo et al, 2002;Quintaes et al, 2002). During this study, we found that the best amplification conditions for RAPD-PCR were an annealing temperature of 35ºC with 3 µL primer.…”
Section: Resultsmentioning
confidence: 79%
“…It does not require any previous knowledge of the DNA sequence of the target organisms, and results in simpler, low-cost, and rapid detection of the genetic variations present in isolated samples (Colauto et al, 2002;Ruiz et al, 2003;Santos and Bäumler, 2004). RAPD has been used as a tool to trace Salmonella epidemiologically, to distinguish Salmonella strains from different geographical origins, and for complementing serotyping and phage typing methods (Soto et al, 1999;De Cesare et al, 2001;Quintaes et al, 2002;Lim et al, 2005;Smith et al, 2011;Rezk et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Uma nítida e peculiar distribuição sazonal é verificada no estado do Pará, já que mais de 70% dos casos da doença são registrados durante o período de intenso calor, entre os meses de julho e dezembro (13,14) .…”
Section: Eletroforese Em Gel De Campo Pulsadounclassified